(untitled) (Research, Society and Development, 2022)
The objective of this study was to analyze the legislation linked to national and state public policies (Paraná), published from 1988 to 2021, which dialogue with the guidelines of self-care for the elderly. The methods used were documentary research of a retrospective and descriptive nature, of primary data, with a survey, organization and analysis of laws and resolutions related to the guidelines of self-care for the elderly. Data collection took place from May to June 2022. For data analysis, Content Analysis was used. The results were 35 normative instruments that address self-care for the elderly, with 12 national laws, a federal resolution, a bill and 21 state laws. From the content analysis, encodings based on the principles of Self-care emerged, according to Orem: health promotion, well-being, protection, leisure, safety and health. It was found that the legislation dialogued with self-care, historically evidencing progress in the dialogue on the subject, but with important gaps, mainly linked to the interests and needs of the elderly. Despite the existence of several initiatives of legislation linked to public policies that dialogue with self-care, legal regulations still do not follow the changes in the profile of this population, remaining, as a challenge, the encouragement of self-care in different population strata.